Reliability and power loss analysis: A case study of a power plant in Nigeria. Issue 1 (1st January 2019) - Kolawole, Adekunle; Agboola, Olayinka Oluwole; Ikubanni, Peter Pelumi; Raji, Olakunle Ganiyu; Okechukwu Osueke, Christian
Abstract: The consequence of electric power outage goes beyond the frustration experienced. Electric power outage could lead to injuries and sometimes deaths especially when it interferes with the elements of daily utility like the powered elevators in towers and life-saving equipment in the hospitals. In this study, an assessment of the reliability of a power generating plant was carried out to provide an opportunity to checkmate frequent fault occurrence and prolonged outages. Historical data were obtained from a generating plant in Nigeria. The data were used to evaluate the overall performance of the plant and its generating units. The results showed reliability results of the six units of the plant as 0.00%, 82.39%, 8.25%, 18.60%, 45.98% and 83.41% for units 1, 2, 3, 4, 5 and 6, respectively, while the overall reliability was 55.73%. The plant's availability and capacity factor were 50% and 35%, respectively. The generation loss analysis indicated that gas restriction, grid constraints and plant unavailability prevented the plant from running at maximum continuous ratings (MCR). It was recommended that to have an optimum operation of the entire system, further study should be extended to the transmission and distribution arms of the power system.